Aerobic Granules: Microbial Landscape and Architecture, Stages, and Practical Implications - Gonzalez-Gil, Graciela (American Society for Microbiology, 2014)
For the successful application of aerobic granules in wastewater treatment, granules containing an appropriate microbial assembly able to remove contaminants should be retained and propagated within the reactor. To manipulate and/or optimize this process, a good understanding of the formation and dynamic architecture of the granules is desirable. Models of granules often assume a spherical shape with an outer layer and an inner core, but limited information is available regarding the extent of deviations from such assumptions. We report on new imaging approaches to gain detailed insights into the structural characteristics of aerobic granules. Our approach stained all components of the granule to obtain a high quality contrast in the images; hence limitations due to thresholding in the image analysis were overcome. A three-dimensional reconstruction of the granular structure was obtained that revealed the mesoscopic impression of the cavernlike interior of the structure, showing channels and dead-end paths in detail. In “old” granules, large cavities allowed for the irrigation and growth of dense microbial colonies along the path of the channels. Hence, in some areas, paradoxically higher biomass content was observed in the inner part of the granule compared to the outer part. Microbial clusters “rooting” from the interior of the mature granule structure indicate that granules mainly grow via biomass outgrowth and not by aggregation of small particles. We identify and discuss phenomena contributing to the life cycle of aerobic granules. With our approach, volumetric tetrahedral grids are generated that may be used to validate complex models of granule formation.